Students’ Anxiety in Delivering English Material Presentation on Online English Study Program Webinar - Ivan Achmad N; Agnes Permata Andesta (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This research was aimed to describe the causes of anxiety faced by students in delivering English presentation material on Webinar in Seminar class and to describe the strategies used by students to overcome the anxiety in delivering English presentation material on Webinar in Seminar class. This research was a quantitative research. Subject of the research was the whole students of English Language Education Study Program of UMB Academic Year 2020/2021 who has delivered English presentation material on Webinar in Seminar Class on January 4th – 10th, 2021. The total subjects are 57 students. The instruments of this research were questionnaire and interview. The questionnaire was divided into two kinds; causes of anxiety and the strategies to overcome anxiety. The questionnaire of strategies used by students to overcome anxiety in presentation is adapted from Kondo & Ling (2004) who divided the strategies into preparation, relaxation, positive thinking, peer seeking, and knowing our audience (resignation). Moreover, to reconfirm the result of questionnaire the researcher did interview to 10 students who got much anxiety while delivering the presentation on Webinar class. There are two findings of this research; first, the causes of anxiety faced by students in delivering English presentation material on Webinar in Seminar class were (1) Webinar as the first online presentation; (2) the time to prepare is to short; (3) the material is not appropriate to the theme choosen; (4) the lecturers join the webinar; (5) Less knowledge related to the material; (6) Lack in Grammar; (7) Speaking full in English; (8) Lack of Pronounciation; (9) Fear of Negative Evaluation; (10) Being Center of Attention. Moreover, the most dominant causes was Fear of Negative Evaluation; Second, the strategies used by students to overcome the anxiety in delivering English presentation material on Webinar in Seminar class were preparation, relaxation, positive thinking, peer seeking, and knowing our audience (resignation). Moreover, the most dominant strategy used by students was preparation. Keywords: Anxiety, Material Presentation, Online Webinar